Habit cough in children. Issue 4 (April 2023) - Liu, Norrice M.; Chadwick, Clare-Louise; Gupta, Atul
Abstract: Cough is one of the most common presenting complaints in childhood. Chronic cough has many possible causes, and this symptom often results in extensive investigations, treatments and anxiety. Habit (habit-tic) and somatic cough disorder (also known as psychogenic cough) is one of the more common underlying diagnoses eventually reached. Habit cough often follows an upper respiratory infection. It is a dry, repetitive, honking, disruptive cough. Characteristically, habit cough usually reduces with distraction, and disappears in sleep. A good detailed history and physical examination, coupled with (normal) basic investigations will usually suffice in diagnosing habit cough – it is important to avoid extensive investigations and unnecessary treatments. However, it is also imperative to note that some children may have both pathological and habit or psychogenic cough. The mainstay of management of habit cough is education and addressing any underlying psychosocial stressors. Various forms of psychotherapies and physiotherapies (cough suppression techniques) have been shown to be effective. With intervention, most children with habit cough will achieve complete resolution, or at least improvement in symptoms. This short article is aimed at healthcare professionals working with children and gives practical advice about investigation and management of suspected habit cough in children and young people.